Semiotika Tanda dan Makna - Efendi, Erwan; Siregar, Irfan Maulana; Harahap, Rifqi Ramadhan (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Semiotics is one of the most interpretive methods of communication research in analyzing texts, and its success or failure as a method rests on how well researchers are able to articulate the cases they study. The semiotic tradition consists of a set of theories about how signs represent things, ideas, circumstances, situations, feelings, and conditions beyond the signs themselves. The study of signs not only provides a way of looking at communication, but has had a strong influence on almost all perspectives of communication theory. The basic concept that unifies the semiotic tradition, the sign which is defined as a stimulus that signifies or denotes some other condition, such as when smoke indicates the presence of fire, a symbol which usually signifies a complex sign with many meanings, including very special meanings. Some experts make a strong distinction between signs and symbols. Signs in reality have a clear reference to something, while symbols do not. Semiotics has the advantage of producing textured "thick descriptions" and complex analyses. Keywords: semiotics, signs and symbols